Naturalizing culture—time for an ecological understanding of “culture” in international culture and sustainability policies - Pyykkönen, Miikka (Frontiers in Political Science, 2024)
The current hegemonic understanding of culture and sustainability leans strongly on the conceptualization of ‘culture’ as profoundly anthropocentric. ‘Sustainability’ in cultural policies again means often the potential of creative industries in contributing to economic growth. This approach can be seen as very problematic in the era of extending the environmental crisis, which urgently calls for not only new kinds of policies on sustainability but also new thinking on the relationship between culture and nature. The main purpose of this article is to analyze how recent theories and concepts concerning the rethinking of nature–culture relationship and ecological citizen-subjectivity could challenge the hegemonic economist sustainability discourse of cultural policies. The article presents the results of discourse analysis on how the economic side of sustainability has recently become the mainstream signification in international cultural policies and what are the major documents and institutions maintaining and strengthening this approach. The discourse analysis focuses on the questions: how is cultural sustainability systematically signified, and what are the arguments and justifications for the main significations the documents make? The data consist of the conventions, declarations, and program papers of the G20, OECD, UN, UNCTAD, UNESCO, and WTO from “Brundtland report” (1987) until now. Theoretically, I go through the recent ideas of social theories on the ecologization of economy, society, culture, and citizenship/subjectivity as proposed by Tim Jackson, Bruno Latour, Andreas Malm, and the Planetary Wellbeing Research Group. I consider how the hegemony of economism and anthropocentrism in cultural policies could be changed with their help.